Processo licitatório e a celebração de parcerias com o terceiro setor - Galil, João Victor Tavares (2020)
The purpose of this paper is to study the obligation to institute a previous bidding process for the celebration of partnerships with the entities that make up the third sector, a sign that, by itself, is the scene of numerous debates and a source of doubts for the doctrine. and for Jurisprudence, especially because of the moment when it was introduced to the national legal universe, marked by political attitudes defending, on a large scale, the imposition of neoliberal ideas about the Social State conceived by the 1988 Constitution, one of them being the state incentive to non-profit entities intended to provide social services in the absence of the state. Strongly influenced by the privatizing ideas of that time, the legal authors began to see a complete fungibility between state and private acts, which even allowed us to affirm that the conclusion of public-private agreements, instruments often characterized by a supposed coincidence of interests, was not constituted by the opening of bidding, unlike what was always done with the administrative contracts. The correct study of the constitutional program reveals the misconception of the conclusion, also assumed by the Federal Supreme Court when analyzing, in one of the most controversial moments of the Court, the constitutionality of the Statute of Social Organizations, which ended up influencing all works on the subject. It analyzes the conflict of the constitutional program against the privatizing ideas of the 90s, the concept of third sector for the national legal doctrine, the administrative performance under the light of the Federal Constitution, as well as the fomentation activity, the legal nature of the agreements with entities and the institute of bidding, as well as analyzing how the legal system, correctly interpreted, behaves before the main legal instruments related to partnerships with the third sector